"Thrown down but not Destroyed". - Unwin, James R. (Novum Testamentum, 2015)
This paper explores the spectacles in the Greek East in an attempt to cast new light on Paul's discourse in 2 Cor 4:7-15. Scenes from gladiatorial munera were not only observed by spectators in theatres, amphitheatres, or stadiums, but were elaborately displayed in commemorative monuments. The emergence of a visual language evoked from these arena scenes offers us another lens to interpret the reception of Paul's polyvalent self-presentation throughout 4:7-15. Paul is convinced that his body is a site where viewers observe, like in the arena, both death and life, and that his performance becomes an exhibition of the crucified Christ.